Thermal NDT research at Tomsk Polytechnic University. Issue 2 (2nd July 2016) - Vavilov, Vladimir P.; Chulkov, Arsenii O.; Derusova, Daria A.; Pan, Yangyang
Abstract: This paper presents a brief history and the current status of research at the Thermal Nondestructive Testing Laboratory of Tomsk Polytechnic University (TPU), Russia. The emphasis of the laboratory research is advanced modelling (analytical and numerical) and data processing, including Fourier and wavelet transform, neural networks, correlation analysis, dynamic thermal tomography, and other methods of thermal NDT. This paper describes experimental tests, practical applications in aviation and energy audits, as well as areas of future research.